Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/plants10091941
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Phytochemical, Antioxidant and Volatile Composition of Pomelo Fruit (Citrus grandis (L.) Osbeck) during Seasonal Growth and Development

Abstract: Citrus fruits exhibit a high level of different phytoconstituents, of which the changes in the different parts of the fruit during ripening have not been thoroughly studied yet. Thus, in this study, we have investigated how different parts of pomelo fruit (Citrus grandis L.) are modified throughout the development of two consecutive growing seasons. In detail, the main phytochemical compounds, such as total phenolic content, total flavonoid content, antioxidant capacity, DPPH free radical scavenging activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 68 publications
(89 reference statements)
4
31
1
Order By: Relevance
“…This result indicated that immature fruits are suitable for the production of citrus products having high antioxidant activity. Similar results have been observed during fruit development stages in various citrus fruits, including Pomelo [ 24 ], sweet orange [ 27 ], Chinese native cultivars [ 28 ], and Navel orange [ 29 ]. The decrease in phenolic compounds according to the fruit development led to a decrease in their antioxidant activities.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…This result indicated that immature fruits are suitable for the production of citrus products having high antioxidant activity. Similar results have been observed during fruit development stages in various citrus fruits, including Pomelo [ 24 ], sweet orange [ 27 ], Chinese native cultivars [ 28 ], and Navel orange [ 29 ]. The decrease in phenolic compounds according to the fruit development led to a decrease in their antioxidant activities.…”
Section: Resultssupporting
confidence: 78%
“…In addition, flavonoids (quercetin triglucoside, saponarin, quercetin triglucoside derivatives, kaempferol triglucoside, hesperetin triglucoside, kaempferol-3-rutinoside, isorhamnetin-3-rutinoside, narirutin, hesperidin, didymin, nobiletin, methoxynobiletin, and tangeretin), volatile compounds (α-pinene, β-pinene, α-terpinene, limonene, γ-terpinene, α-terpinolene, linalool, 4-terpineol, α-terpineol, decanal, δ-elemene, α-cubebene, texanol, α-copaene, β-elemene, γ-elemene, α-humulene, germacrene D, α-farnesene, and δ-cadinene), limonoids (zapoterin, xylogranatin K, nomilin, and limonin), and carotenoids (β-carotene and β-cryptoxanthin) were identified as the secondary metabolites. Similar metabolite profiles have also been observed during fruit development in other citrus varieties, including Navel orange [ 8 ], Ponkan [ 10 ], Persian Lime [ 11 ], and Pomelo [ 24 ].…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…C. pepo seeds oil has no cholesterol, and is rich in ω9, and ω6 acids, fatty acids with more than 40% oleic acid, 33.1% linoleic acid, and 14.7% palmitic acid, and is effective in relieving joint pain, especially in chronic conditions and post-menopausal bone density [2,3]. The quantity, and quality of secondary metabolites such as alkaloids, glycosides, steroids and, essential oils in medicinal plants are affected by environmental factors including drought stress, nutrition, and plant growth regulators [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[7,17]. Several studies have also shown that drought had beneficial impacts on secondary metabolite biosynthesis, solute accumulation, and enzyme activity [5,[8][9][10][18][19][20][21][22]. Cultivation of drought-tolerant genotypes of medicinal and aromatic plant species, on the other hand, could be another way to address water scarcity issues.…”
Section: Introductionmentioning
confidence: 99%